Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_317_324
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Grain Growth in Directional Solidification of a Nickel-Base Superalloy

Abstract: The structure evolution of bi-crystal samples during directional solidification was explored. It was found that in the case of diverging dendrites the better aligned grains overgrew the misaligned grains by means of the dendrite development from the better aligned grains. However, in the case of converging dendrites the result differs in two ways from the prediction of the generally accepted model for competitive grain growth. First, the misaligned dendrites are able to overgrow the better aligned dendrites. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The crystallographic orientation (see Figure 7 ) was generated by assuming a fibre texture in which all grains have a <100> direction oriented near the z axis—the perpendicular directions being quasi-randomly oriented. This texture corresponds to the typical texture obtained in DS FCC alloys [ 8 , 9 , 14 ]. The particular Euler angles (using the Bunge convention) used to generate the fibre texture are = 20 ± 90 , = 0 ± 4 , = 32 ± 20 .…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The crystallographic orientation (see Figure 7 ) was generated by assuming a fibre texture in which all grains have a <100> direction oriented near the z axis—the perpendicular directions being quasi-randomly oriented. This texture corresponds to the typical texture obtained in DS FCC alloys [ 8 , 9 , 14 ]. The particular Euler angles (using the Bunge convention) used to generate the fibre texture are = 20 ± 90 , = 0 ± 4 , = 32 ± 20 .…”
Section: Methodssupporting
confidence: 74%
“…Therefore, in the aerospace industry, DS alloys are of great interest because of the pair price/performance, being that they are cheaper and easier to manufacture than SXs and with superior mechanical properties than polycrystals. Their microstructure is characterised by columnar grains, aligned with the principal-stress axis (-z- axis by convention), that grow in the preferred crystallographic orientation <001> [ 8 , 9 ], leading to considerable anisotropy when the loading changes from the solidification direction to the perpendicular one. Different approaches have been used to model the constitutive response of heterogeneous structures of this type, going from transversally isotropic viscoplastic models [ 10 , 11 ], through the use of self-consistent schemes [ 12 , 13 ], to the crystal-plasticity-finite-element method (CPFEM) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, during the process of competitive grain growth, the favourably oriented grain A 2 overgrows the unfavourably oriented grain B. Recently, Zhou et al 22 22,23 reported that the misaligned grains were able to overgrow the better aligned grain by blocking the dendrites of the better aligned grains at the grain boundary. Zhao24 has found similar results about the grain competitive growth.…”
Section: Resultsmentioning
confidence: 99%
“…Schematic illustration of Walton and Chalmers model for competitive grain growth: 22 22,25 grains A and B are favourably and unfavourably oriented respectively…”
Section: Resultsmentioning
confidence: 99%
“…Expecially, spiral grain selection method was the most basic in the process of preparing single crystal superalloy blade and it also has been widely used in producing all kinds of single crystal material [1,2]. The growth regularity of the different alloy system has been studied by different methods, and the results suggested thatgrain competitive growth and eliminationmechanism was different [3][4][5][6][7]. The grains with <001> orientation have the advantage of preferential growth because the single crystal alloy IC6SX is face-centered cubic structure.…”
Section: Introductionmentioning
confidence: 99%